The Design of a Conceptual Model of Learning Outcomes in the Computer-based Sport training (CBST). - P Iskandar, Yulita Hanum (Universiti Sains Malaysia, 2014)

(untitled)
Instructional design usually begins with the specification of behavioral objectives or intended learning outcomes. The field of educational psychology has long been sensitive to the desirability of establishing learning objective for instruction.